Analisis Kepuasan Pelanggan Terhadap Kualitas Layanan Perbaikan Jaringan Internet dengan Metode Servqual dan IPA di PT MKM - Fitriani, Rohmah; Roswandi, Iwan; Junaedi, Didi (Proceeding Mercu Buana Conference on Industrial Engineering, 2023)
PT MKM is responsible for installing the customer's internet network up to repairing the internet network. The existence of an internet network repair service is used to ensure that the internet network at the customer's home can be used stably and smoothly. To ensure customers get good service and do not switch to other providers, PT MKM must pay attention to the services provided to its customers. The purpose of this study was to measure the value of customer satisfaction on the quality of network repair services and to determine the priority for repair service improvements at PT MKM. This study used servqual and IPA methods with 50 respondents participating in answering the questionnaire. The results show that the GAP value in each statement is negative with the largest GAP value being on the assurance dimension of -1.18 and the lowest GAP being on the responsiveness dimension of -0.76. Of the 10 indicators distributed into 4 quadrants, the main priority for improvement that must be improved using the IPA method is attribute P5 which is in quadrant I.